Information services for melanoma patients and awareness among those affected Informationsangebote für Melanompatienten und ihre Bekanntheit unter Betroffenen - Bruetting, J.; Bergmann, M.; Weber, C.; Berking, C.; Tilgen, W.; Schadendorf, Dirk; Meier, F. (Hautarzt, 2018)
Background: Besides medical consultations, various sources of information and support are available for melanoma patients (MP) in Germany from commercial and non-commercial providers; however, little is known about how they are perceived and accepted by MPs. Material and methods: Between July and October 2016 a total of 529 melanoma patients were surveyed at 27 accredited German skin cancer centers by means of a standardized questionnaire. Their awareness and satisfaction with 12 given sources of information and counseling services (print, online and by telephone) were surveyed. The sources were recommended by renowned providers from the field of (dermatological) oncology for use by MPs. Results: The MPs reported that the booklets called The blue advisor – skin cancer (Die Blauen Ratgeber – Hautkrebs, 43%) and Patient guidelines melanoma (Patientenleitlinie Melanom 24%) and the online domain www.hautkrebs-screening.de (23%) were the best known sources. These also met the information needs of the majority of users (65–80%). Booklets from commercial providers (between 8–16% known) were satisfactory for 42–56% of users. At 14% and 11%, respectively, the cancer counseling services (Krebsinformationsdienst) and INFONETZ Krebs as mainly telephone advisory offers were less well known. Few MPs were familiar with the skin cancer or melanoma booklets of the Austrian Cancer Aid and the Swiss Cancer League (2% each). Conclusion: The increased awareness and acceptance of booklets as well as information from principally non-commercial providers suggest that they are more often mediated to MPs and more frequently used and accepted by those affected.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Booklets; Information seeking behavior; Internet; Patient education; Questionnaires